Meningkatkan Kemampuan Literasi Digital Guru PAUD Dalam Pendistribusian Informasi Melalui Pelatihan Model In House Training (IHT) Di RA At-Taqwa Tarogong-Garut - Ulfah, Fitria; Fauziyah, Fithri (LP2M STAI Al-Musaddadiyah Garut, 2025)
This research is motivated by the understanding of digital literacy of teachers at RA At-Taqwa Tarogong Kidul-Garut for the 2023-2024 academic year which is still relatively low at a percentage of 33.3%. Aims to improve the digital literacy skills of preschool teachers in distributing information through In House Training (IHT) model training at RA At-Taqwa Tarogong-Garut. The research method used in this research is collaborative action research using the Kemmis and Mc.Taggart model. The subjects of this research were six teachers at RA At-Taqwa Tarogong Kidul-Garut. Data collection techniques used were observation, interviews and documentation. The research was carried out in three cycles and each cycle consisted of two meetings with planning, action, observation and reflection procedures. Data collection techniques in this research are through observation, interviews and documentation. Meanwhile, the data analysis technique in this research uses data triangulation techniques. The research results show that teachers' literacy understanding increases in each cycle. So it can be concluded that In House Training (IHT) model training can improve the digital literacy skills of teachers at RA At-Taqwa Tarogong-Garut. This was marked by an increase in the percentage of teacher success, which initially was 33.3% in cycle 1, increased to 50% in cycle 2, and 83.3% in cycle 3. Keywords: In House Training (IHT); Digital Literacy; PAUD Teacher; Information Distribution Competency.